Ultrafast dynamics of differently aligned COOH-DTE-BODIPY conjugates linked to the surface of TiO2. (5th January 2018) - Schweighöfer, Felix; Yüce, Imanuel; Dworak, Lars; Guo, Peng; Zastrow, Marc; Mayer, Kerstin; Barta, Christoph; Liebmann, Diana; Ziebart, Nandor; Rück-Braun, Karola; Wachtveitl, Josef
Abstract: The photoinduced dynamics of two DTE-BODIPY conjugatesA, B with carboxylic acid anchoring groups coupled to the surface of TiO2 were studied by ultrafast transient absorption spectroscopy. For compoundA, with an orthogonal orientation of the BODIPY chromophore and the photoswitchable DTE unit, a charge separated state could not be reliably detected. Nevertheless, besides the energy transfer from the BODIPY to the ring-closed DTE-c, indications for an electron transfer reaction were found by analyzing fluorescence quenching on TiO2 in steady state fluorescence measurements. For compoundB with a parallel orientation of chromophore and photoswitch, a charge separated state was conclusively identified for the coupled dyad (TiO2 ) via the observation of a positive absorption signal (at λ pr > 610 nm) at later delay times. An electron transfer rate of 7 × 10 10 s −1 can be extracted, indicating slower processes in the dyads in comparison to previously published electron transfer reactions of DTE compounds coupled to TiO2 .